La necesidad de incorporar al código orgánico de la niñez y adolescencia la tenencia compartida de menores - Urvina Ocampo, Leyton Adrian (2017)
Shared Tenure is a legal concept that has gained strength recently as a mechanism to resolve conflicts or more equitably responsibilities are delegated to parents regarding the care and custody of her children. If we start from the premise that the obligations and responsibilities regarding the child are the father and mother so stipulated in Article 100 of the Code of Children and Adolescents. The Constitution of the Republic in Art. 66 paragraph 4, it establishes the constitutional right to equality before the law but that vanishes when a break or separation of parents in an automated way as it occurs, custody of minors is by the mother according to the rules laid down in Article 108 third paragraph paragraph 1) of the Civil Code. This has determined that one of the parties get an advantage, if we consider that parental obligations must be equal with regard to rights must be in the same proportion established as visits, custody decisions, that is where one of the solutions to such conflicts is shared tenure. In our country has begun through male moves the debate on this issue but practically there is little legal contribution or studies that allow viable such proposals that would improve the coexistence between parents and society which is itself one of the purposes of laws. This research will take into account the different social and legal variants around Tenure, the effects this generated by the dispute over child custody or less, for lack of other legal elements leading to the best compromise solution about the rights and responsibilities of parents over their children. Therefore the problem to investigate the as follows: "The inflexibility of the right to custody of children generates these feel little emotional affection for one parent and therefore this causes negative effects on their social future". For these reasons, I believe that a reform of the current Organic Law on the Family, Women, Children and Adolescents, specifically Title III Tenure would be necessary as this problem should be investigated facilitating the introduction of new alternative solutions to the same .